Odpowiedzi

Najlepsza Odpowiedź!
2009-12-21T17:40:31+01:00
A) 2x+3y=0,5
3x+y=-1 /-3
2x+3y=0,5
-9x-3y=3
-7x=3,5
x=-2
3x+y=-1
3(-2)+y=-1
y=5


a) 2x+3y=0,5
3x+y=-1
y=-3x-1
2x+3y=0,5
2x+3(-3x-1)=0,5
-7x=3,5
x=-2
y=-3x-1
y=-3(-2)-1
y=6-1
y=5
metoda przeciwnych współczynników
b)2x+y=14
8x+ 1/2y=35

2x+y=14 /-4
8x+ 1/2y=35

-8x-4y=-56
8x+ 1/2y=35
-3,5y=-21
y=6
2x+y=14
2x+6=14
2x=8
x=4

b)2x+y=14
8x+ 1/2y=35
y=-2x+14

8x+ 1/2(-2x+14)=35
8x-x+7=35
7x=28
x=4
y=-2x+14
y=-2*4+14
y=6
metoda przeciwnych współczynników
c)3x+4y=2
5x+7y=1

3x+4y=2 */-5
5x+7y=1 */3
-15x-20y=-10
15x+21y=3
y=-7
3x+4y=2
3x+4*(-7)=2
3x=30
x=10

c)3x+4y=2
5x+7y=1
3x=-4y+2
x=-4/3y+2/3

5x+7y=1

5(-4/3y+2/3)+7y=1
-20/3y+21/3y=-10/3+1
y=-7

5x+7y=1
5x+7*(-7)=1
5x=50
x=10
zdecydowanie metoda przeciwnych współczynników






1 5 1